S4nDb0x
Rozwiązane

Proszę o jak najszybszą pomoc!



Proszę O Jak Najszybszą Pomoc class=

Odpowiedź :

[tex]\left \{ {{3(x+1) - (y-2) = 9} \atop {2x + y =6}} \right. \\\\\left \{ {{3(x+1) - (6-2x-2) = 9} \atop {y = 6 - 2x}} \right. \\\\\\left \{ {{3x+3 - 6+2x+2 = 9} \atop {y = 6 - 2x}} \right. \\\\\\\left \{ {{5x = 9 - 3 + 6 - 2} \atop {y = 6 - 2x}} \right. \\\\\\\left \{ {{5x = 10} \atop {y = 6 - 2x}} \right. \\\\\\\\\left \{ {{x = 2} \atop {y = 2}} \right. \\\\[/tex]

Sprawdzenie:

3*3 - 2 - 2 = 9

9 = 9

2*2 + 2 = 6

6 = 6